Mixed Epithelial and Stromal Tumor of the Kidney or Adult Mesoblastic Nephroma : An Update - Moslemi, Mohammad Kazem (Urology Journal, 2010)
PURPOSE: Our aim was to review the spectrum of usual and unusual clinical and morphologic findings observed in mixed epithelial and stromal tumor of the kidney (MEST). MATERIALS AND METHODS: On the basis of MEDLINE database searches, we assessed all aspects of MEST or adult mesoblastic nephroma since the first report in 1997 till the end of 2009. RESULTS: Mixed epithelial and stromal tumor is a relatively rare and distinct neoplasm of the kidney that should be distinguished from other renal neoplasms. Although the overall prognosis is favorable, recurrence and malignant transformation of MEST can occur CONCLUSION: It is difficult to distinguish benign or malignant nature on imaging studies.